Metaphysics, Natural Science and Theological Claims: E. J. Lowe's Approach - Guta, Mihretu Petros (TheoLogica, 2021)
In this paper, I aim to discuss E. J. Lowe's view of the synergy between metaphysics and natural science. In doing so, I will extend Lowe's synergistic model to develop a realist account of theological claims thereby responding to Byrne's strong form of eliminativism and agnosticism about theological claims. The paper is divided up as follows. In section 1, I will discuss Lowe's view of metaphysics. In section 2, I will explain how Lowe thinks metaphysics and natural science are related. In section 3, I will respond to objections against Lowe's conception of metaphysics. In section 4, I will discuss the implications of Lowe's conception of metaphysics for a realist account of theological claims. In section 5, I will conclude this paper by claiming that there are excellent reasons to extend the synergy between metaphysics and natural science to that of theology as well.